Prevalence of Anemia in Community-Acquired Pneumonia Patients: Anemia Prevalence in Hospitalized Pneumonia Patients - Saeed, Samina; Yaqub, Muhammad Usman; Ghayyur, Aysha; Siddique, Shazia; Anwar, Muhammad; Afzal, Ayesha (Pakistan BioMedical Journal, 2024)
The frequency of anemia in intensive care units is well documented. Less is known, however, about the prevalence of anaemia in hospitalised patients with community-acquired pneumonia, which is one of the common reasons for hospitalisation, affecting both healthy and co-morbid individuals and is usually not accompanied with acute blood loss. Objective: To determine the frequency of anemia in patients presenting with pneumonia. Methods: This descriptive cross-sectional study was conducted with pneumonia patients at Department of Medicine Pulmonology in HDU/ICU Jinnah Hospital, Lahore curing thr period of three months. The 345 subjects with mean age 44.4 ± 9.4 (range: 20 – 60) years, male to female ratio 1:1.12, diagnosed with pneumonia underwent assessment of hemoglobin levels at presentation. Relationship between anemia and other co-morbidities has been evaluated that included duration of pneumonia, obesity, diabetes mellitus and hypertension. Results: The mean duration of pneumonia symptoms was 8.7 ± 6.9 (range: 2-25) days whereas the mean hemoglobin concentration was found 12.3 ± 6.9 g/dL ranged from 7.1 –14.6 g/dL. The prevalence of anemia was found to be 37.7% and 215 (62.3%) of the 345 patients have shown normal hemoglobin levels. Female gender, higher age, greater duration of pneumonia symptoms and presence of diabetes mellitus significantly correlated with anemia in pneumonia (p-value < 0.05). Whereas, obesity did not have any significant effects on anemia in pneumonia (p-value > 0.05). Conclusions: Anemia was present in significant number of patients with pneumonia and was associated with female gender, Diabetes ,Hypertension and prolonged duration of pneumonia.